(untitled) - Pharr, Donald (Boston, 2005)
"Writing Today: Contexts and Options for the Real World", brief edition is a text designed to help students see reading and writing as practical tools both in college and in the world of work.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Rhetoric,Grammar,Ngữ pháp,Tu từ học